2018
DOI: 10.1371/journal.pone.0198516
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide screen reveals important roles for ESCRT proteins in drug/ion resistance of fission yeast

Abstract: To study sodium homeostasis, we performed a genome-wide screen for deletion strains that show resistance to NaCl. We identified 34 NaCl-resistant strains. Among them, the largest group that consists of 10 genes related to membrane trafficking and 7 out of 10 genes are ESCRT proteins which are involved in cargo transportation into luminal vesicles within the multivesicular body. All of the ESCRT related mutants which showed sodium resistance also showed defects in vacuole fusion. To further understand the role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Several genome-scale chemogenomic analyses have been performed to look at 5-FU responsiveness in fission yeast [ 16 , 41 , 42 , 43 ], but none of these null mutants of Ino80 complex subunit genes were observed to exhibit resistance against the drug. Ino80 complex, an ATP-dependent nucleosome-remodeling complex, was shown recently to regulate the integrity of constitutive heterochromatin, which encompassed the centromere of the fission yeast to confer stable kinetochore attachment to spindle microtubules for proper chromosome segregation during the M-phase of the cell cycle [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Several genome-scale chemogenomic analyses have been performed to look at 5-FU responsiveness in fission yeast [ 16 , 41 , 42 , 43 ], but none of these null mutants of Ino80 complex subunit genes were observed to exhibit resistance against the drug. Ino80 complex, an ATP-dependent nucleosome-remodeling complex, was shown recently to regulate the integrity of constitutive heterochromatin, which encompassed the centromere of the fission yeast to confer stable kinetochore attachment to spindle microtubules for proper chromosome segregation during the M-phase of the cell cycle [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…g . mutant growth is sensitive to MnCl 2 and steady–state CPY maturation is reduced [ 52 54 ] ( S1 Fig ). When studying these vps36 Δ cells after methionine addition, we found that Mup1-GFP follows a similar trajectory from the plasma membrane to vacuole lumen ( Fig 1B ), albeit with two important exceptions: (1) Large Mup1-GFP and FM4-64 –positive puncta appeared adjacent to vacuole membranes, a hallmark phenotype of ESCRT deletion mutants (VPS class E) [ 55 ], confirming ILV formation was blocked at endosomes in these cells, and (2) Mup1-GFP aberrantly accumulates on vacuole membranes on route to the lumen ( Fig 1B and 1C ), which is not a trafficking intermediate of the MVB pathway.…”
Section: Resultsmentioning
confidence: 99%
“…Signatures of Schizosaccharomycetes have been found in metagenomic surveys of marine environments in the past (e.g., Porites astreoides coral from the Caribbean Sea in Wegley et al, 2007, and Avicennia marina mangroves from the Red Sea in Simões et al, 2015). These observations are remarkable, as fission yeast is not known to be especially salt tolerant (e.g., Yang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%